Biomechanical Device for Measurement of Adductors Strength and Aid in Self-Catheterisation of Spastic Patients - Maria Cruz; Vítor Maranha; Fernando Moita; Nuno Cruz; Deolinda Rasteiro; Filipe Carvalho; Jorge Lains; Luis Roseiro (Designs, 2022)
Intermittent vesical self-catheterisation is a legitimate and safe technique that has been reported since the 1970s as a solution for the treatment and prevention of vesical urinary complications resulting from spinal cord injury. This practice, using clean technology, has been asserting itself as one of the best alternatives for people with neurogenic bladder. However, adherence is not complete due to some barriers imposed to this procedure by the injured, with emphasis on positioning, agility, and visual impairment. The solutions presented today to support self-catheterisation are expensive equipment that does not allow patients with advanced levels of spasticity to have their autonomy. A biomechanical support device was developed to aid self-catheterisation, mainly aimed at women with spasticity, filling the gap in the existing products. Despite the main objective of self-catheterisation, the system’s design made it possible to quantify the strength of the adductors for the sitting position during the execution of the adduction movement, particularly relevant for spastic patients. The device’s production was entirely carried out using the FDM methodology, with 3D printers, and its design and operation were thought to overcome the physical and psychological barriers imposed by the users. The system was first tested with a group of healthy volunteers to obtain a pattern of the adductors force in a sitting position and after with a group of spastic volunteers. The obtained data allows to compare the adductor force data and optimize the system, with particular functionalities for spastic patients, with the implementation of a motorised version and a visualization camera. The system, its developments, and results obtained are present and discussed.